Gender in Management: A Sociological Perspective - Palmer, Gill; Kandasaami, Tamilselvi (Accounting Department,, 1997)
Thispaper starts with an overview of the literature on gender differences in managerial bahaviour. Much of the research on management ignores or denies any difference between genders. On the other hand, research on management style and gender stereotypes demonstrates that there are real differences in culturally approved communication and interpersonal influence methods used by men and women (Palmer, 1993; Willis, 1990). Empirical findings from a study on women small business owners is used to explain androgyny. We review the evidence for the existence of a ’glass ceiling’ causing discrimination against women in management. We then suggest a theoretical framework of the management process which can be used to analyse the various ways that gender stereotypes impact on the management processes used within management.When we talk about gender in management, few people would say that women have made great strides in every walk of life. Since the 1970s women have succeeded in combining careers with families and are moving into male-dominated professions such as law, industry and commerce, but are still not well represented in the more senior positions (Grimwood & Popplestone, 1993). In order to explain this phenomenon we will be discussing the sociological constuction of women and men as genders, ‘women’ and ‘men’ and ‘masculinity’ are socially and culturally produced and vary with the society and the social context (Symons, 1992). For many years, men were able to hold power at all levels because they were free of childbearing and child rearing responsibilities and so available to participate in social and political life.